FAB531 : 3D layout / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This course introduces students to the concept of 3D computer animation. Through practice and analysis, students will develop an understanding of the essential principles of 3D animation which includes perspective, transformations, geometric and spline-based modelling, lighting, camera work, rendering, and modelling natural phenomena and motion through hands-on experience by utilizing computer tools and application. Concurrently, this course works alongside with the principles of animation.